Situation Report: Hungary, 30 April 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Book that Was Never Written The Hungarian National Assembly's Spring Session Endeavors to Develop Hungarian-American Economic Relations Expanding the Relations between Hungarian and Austrian Co-Operatives Tito's Visit to Hungary Foreign Demand for Hybrid Pigs Increases